Isolated Torsion of Accessory Fallopian Tube in a Young Adolescent - Rottenstreich, Misgav; Smorgick, Noam; Pansky, Moty; Vaknin, Zvi (Journal of pediatric & adolescent gynecology, 2016)
Accessory fallopian tube is a rare anatomical variation, which might rarely cause gynecological complications such as infertility, ectopic pregnancy, cystic swelling, and pyosalpinx. It is usually diagnosed by surgeons during diagnostic laparoscopy for other purposes. We present a rare case of isolated accessory tube torsion in a young adolescent. A 16-year-old virgin teen presented with a 24-hour history of aggravating right lower-quadrant abdominal pain and nausea without vomiting or fever. On examination she had right lower quadrant abdominal tenderness with no peritoneal signs. On pelvic ultrasound a right corpus luteum cyst was suspected, but right adnexal torsion could not be ruled out. On laparoscopy, torsion of the right accessory tube was diagnosed. Because of its ischemic and bluish appearance it was removed. The postoperative course was uneventful. Pathology confirmed the diagnosis. Torsion of an accessory fallopian tube is rare. An English literature search showed that the current case is the third reported overall and the first in a young adolescent. Because of the rarity of this congenital variation, and the low suspicion index for its existence, the diagnosis of accessory tube is often missed. Preventive removal of such findings should be considered but weighed against its possible surgical complications.